2018
DOI: 10.1371/journal.pone.0193947
|View full text |Cite
|
Sign up to set email alerts
|

Retinal guanylyl cyclase activating protein 1 forms a functional dimer

Abstract: Retinal guanylyl cyclases (RetGCs) in vertebrate photoreceptors are regulated by the guanylyl cyclase activator proteins (GCAP1 and GCAP2). Here, we report EPR double electron-electron resonance (DEER) studies on the most ubiquitous GCAP isoform, GCAP1 and site-directed mutagenesis analysis to determine an atomic resolution structural model of a GCAP1 dimer. Nitroxide spin-label probes were introduced at individual GCAP1 residues: T29C, E57C, E133C, and E154C. The intermolecular distance of each spin-label pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 48 publications
4
53
0
Order By: Relevance
“…NCS proteins can form dimers, and the process may be dynamically influenced by the presence of cations [36]. Since it was recently proven that bovine GCAP1 acts as a functional dimer [37], we tested whether human GCAP1 variants showed similar oligomeric properties under GC activating/inhibiting conditions. To assess the quaternary structure of the GCAP1 variants we employed a combination of dynamic light scattering (DLS) and analytical size exclusion chromatography (SEC).…”
Section: Quaternary Structure and Aggregation Propensity Of Gcap1 Varmentioning
confidence: 99%
“…NCS proteins can form dimers, and the process may be dynamically influenced by the presence of cations [36]. Since it was recently proven that bovine GCAP1 acts as a functional dimer [37], we tested whether human GCAP1 variants showed similar oligomeric properties under GC activating/inhibiting conditions. To assess the quaternary structure of the GCAP1 variants we employed a combination of dynamic light scattering (DLS) and analytical size exclusion chromatography (SEC).…”
Section: Quaternary Structure and Aggregation Propensity Of Gcap1 Varmentioning
confidence: 99%
“…The GCAP1-modulated RetGC1 transduction system also exists in the olfactory bulb (Duda et al, 2001 ). GCAP1, GCAP2 and GCAP5 each form a dimer in solution (Ermilov et al, 2001 ; Lim et al, 2017 , 2018 ) that binds to dimeric RetGC1 (Liu et al, 1997 ; Ramamurthy et al, 2001 ). The GCAPs activate RetGCs at low Ca 2+ levels in light activated photoreceptors (Peshenko and Dizhoor, 2006 ; Lim et al, 2009 ), whereas Ca 2+ -bound GCAPs inhibit RetGCs at high Ca 2+ levels in dark-adapted photoreceptors (Dizhoor and Hurley, 1996 ; Dizhoor et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this review article, I discuss the recent atomic-resolution structures of dimeric forms of recoverin (Myers et al, 2013 ), GCAP1 (Lim et al, 2018 ), GCAP2 (Pettelkau et al, 2012 ), GCAP5 (Lim et al, 2017 ) and VILIP1 (Li et al, 2011 ) that each adopt very different quaternary structures (Figure 2 ). While the tertiary structures of each monomeric subunit are somewhat similar, the distinct quaternary structures and unique subunit packing arrangement at each dimer interface may play a role in facilitating target recognition and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism of GCAP activation at lowered Ca 2+ concentrations involves the binding of Mg 2+ [ 32 ] to EF-2 and EF-3, thereby inducing a conformational change; the role of EF4 is unclear. In contrast to the case for recoverin, the overall change in tertiary structure for GCAP1 is relatively small [ 33 ]; in particular, the myristoyl group in GCAP1 remains fully buried in both states [ 34 36 ]. GCAP2 is also myristoylated, but whereas the removal of the myristoyl group results in a sevenfold reduction in activity of GCAP1, it has little effect on GCAP2 [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has shown that GCAP1 forms a functional homodimer [ 33 ], suggesting a 2 : 2 stoichiometry of interaction with the GC homodimer. In vitro experiments with mammalian proteins have shown that GCAP1 and GCAP2 are able to activate the two GCs, GC-E and GC-F, with comparable efficacy.…”
Section: Introductionmentioning
confidence: 99%